Kritik Atas Pandangan Penulis Barat Tentang “Islam Liberal”: (Studi Atas Karya Leonard Binder dan Charles Kurzman) - Tiar Anwar Bachtiar (LPPM IAIN Sultan Amai Gorontalo, 2016)
The term Liberal Islam has long been developing. However, in defining many crisscrossing. Therefore, it is important to explore this term from the origin term source, ie of Western writers. This article will describe the two main sources of Liberal Islam discourse is often a reference and is regarded as bearers of Liberal Islam terms, those are“Islamic Liberalism: A Critique of Development Ideologies” by Leonard Binder and “ Liberal Islam: A Source Book” by Charles Kurzman et al. Searches through the two main sources above and compare it with some relevant sources can be concluded that the term Liberal Islam is meant by Binder are those which believed that no textual interpretation of the Qur'an, but the interpretation is based on the essence of the meanings, not what is written in the text. Search essential meaning, not textual that is considered to be able to adapt with the times. Meanwhile, according Kurzman Liberal Islam is that which has the first character, critical of Islam customs and Islamic traditions Revivalists which causes backwardness of Muslims. Second, the desire for progress by promoting the values of Islam which is in line with the values of Western liberalism such as democracy, economic progress, human rights, gender equality, and so on.